Anaesthetic management of parturients with univentricular congenital heart disease and the Fontan operation. (December 2016) - Monteiro, R.S.; Dob, D.P.; Cauldwell, M.R.; Gatzoulis, M.A.
Highlights: Eight women with the Fontan operation delivered 14 live babies between 1994 and 2015. Fontan physiology is described in detail. A neuraxial catheter technique was used in 86% and no patient had general anaesthesia. Postpartum haemorrhage occurred in 50%. Complications: arrhythmia (29%), chest pain (14%), prematurity (71%), IUGR (57%). Abstract: Women with a single ventricle circulation palliated with the Fontan operation require specialist multidisciplinary management. We report 14 such cases with successful pregnancies and detail the pathophysiology encountered. A combined obstetric and cardiac service between Chelsea and Westminster Hospital and Royal Brompton Hospital provides care for women with heart disease, and maintains a prospective database of referred women. We searched this database for women with a known Fontan circulation and reviewed the case notes and electronic patient records between January 1994 and December 2015. Eight women palliated with the Fontan operation delivered 14 live babies over the study period, with detailed peripartum management available for 11. Low-dose combined spinal-epidural or epidural labour analgesia was the intended mode of analgesia or anaesthesia for all deliveries (depending on clinical scenario and clinician preference), and was performed in 79%. Seven cases (50%) had a caesarean delivery. A neuraxial catheter technique was preferred (86%), whether or not vaginal delivery was attempted first. There were no deliveries under general anaesthesia. Fifty percent of cases were complicated by postpartum haemorrhage. Other peripartum complications included arrhythmias (29%), chest pain (14%) and intrauterine growth restriction (57%). Women with a Fontan circulation are increasingly encountered in obstetric practice. A good understanding of the underlying anatomy and its impact on physiology, coupled with meticulous care are essential to allow safe delivery for mother and baby. Multidisciplinary input into peripartum care is required, with anticipation of increased risk of complications such as haemorrhage and arrhythmias.